2020
DOI: 10.3390/coatings10060569
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photochromic Performance of Homogeneous Phase Nitrocellulose Membrane Grafting Spirooxazine Moieties

Abstract: The synthesis of 1,3,3-trimethyl-9′-acryloxyspiro[indoline-2,3′(3H)naphtho[2,1-b][l,4]-oxazine] (AISO) was carried out by catalytic esterification of 1,3,3-trimethyl-9′-hydroxyspiro-[indoline-2,3′(3H)naphtho[2,1-b][l,4]oxazine] (SO–OH) and acrylic acid in the presence of 1,3-dicyclohexylcarbodiimide (DCC) and N-dimethylaminopyridine (DMAP). Then, the synthesis of the target copolymer (NC-g-AISO) was was carried out by benzoyl peroxide (BPO)-induced graft copolymerization of the AISO monomer onto nitrocellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…It is versatile and efficient in a variety of fields in medicine, including water filtration, power generation, catalysis coatings. 17 Recently various reports showed the application of NC and derived blends as a propellant due to its explosive nature. Liu C et al prepared graphene oxide/NC membrane and further, they used as as solid propellant micro thruster by using laser ignition combustion treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is versatile and efficient in a variety of fields in medicine, including water filtration, power generation, catalysis coatings. 17 Recently various reports showed the application of NC and derived blends as a propellant due to its explosive nature. Liu C et al prepared graphene oxide/NC membrane and further, they used as as solid propellant micro thruster by using laser ignition combustion treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been utilised for a variety of coating applications, including coating components, stabilisers, coating membranes, paints, lacquers, varnishes for wood, paper metal, inks for package printing, and celluloid printing. It is versatile and efficient in a variety of fields in medicine, including water filtration, power generation, catalysis coatings 17 . Recently various reports showed the application of NC and derived blends as a propellant due to its explosive nature.…”
Section: Introductionmentioning
confidence: 99%
“…[326] Optical materials that respond to multiple wavelengths can be achieved via electrostatic interactions between light-responsive cellulosic materials and CDs. [328] By combining photoresponsive cellulose and CDs, photo-triggering, reversible Reversible photo-responsive groups CNC, CNF, microcrystalline cellulose (MCC), carboxymethyl cellulose (CMC), HPC [318,[321][322][323] Cotton, filter paper, MCC, cellulose acetate (CA) [324][325][326] Nitrocellulose, MMC derivative Spirooxazine [327,328] CNC, CNF [329] Irreversible photo-responsive groups…”
Section: Light-responsive Cellulosic Materials By Chemical Modificationmentioning
confidence: 99%
“…Further, Sun et al. reported the fabrication of the nitrocellulose membranes with high photochromic properties by the grafting of spiropyran-based acrylate polymers on nitrocellulose through radical polymerization techniques, where an improvement in thermal color decay stability was observed . Some of those methods often involve harsh reaction conditions, lower efficacy, or uncontrolled polymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…40 Further, Sun et al reported the fabrication of the nitrocellulose membranes with high photochromic properties by the grafting of spiropyranbased acrylate polymers on nitrocellulose through radical polymerization techniques, where an improvement in thermal color decay stability was observed. 44 Some of those methods often involve harsh reaction conditions, lower efficacy, or uncontrolled polymerizations. Further, in most of those cases, either hydrophobicity or stability or mechanical property improvements were observed, while combined improvements of most of the crucial properties have been reported rarely, if at all.…”
Section: Introductionmentioning
confidence: 99%